2018
DOI: 10.2478/raon-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma in patients over 70 years of age

Abstract: BackgroundGlioblastoma has in last 20 years seen the steady increase of incidence, which is most prominent in the group of older patients. These older than 70 years have significantly poorer prognosis than other patients and are considered a distinct group of glioblastoma patients. Modified prognostic factors are being used in these patients and this information is lately supplemented with the genetic and epigenetic information on tumour. The therapy is now often tailored accordingly. The aim of our study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
(19 reference statements)
2
7
0
Order By: Relevance
“…The increasing number of elderly patients with GBM corresponded to the increase in life expectancy. A study by Smrdel et al found that the average age of patients diagnosed with GBM was 73 years of age [25]. Likewise, in our cohort, the average age of patients diagnosed with GBM was 72.6 years of age.…”
Section: Discussionsupporting
confidence: 68%
“…The increasing number of elderly patients with GBM corresponded to the increase in life expectancy. A study by Smrdel et al found that the average age of patients diagnosed with GBM was 73 years of age [25]. Likewise, in our cohort, the average age of patients diagnosed with GBM was 72.6 years of age.…”
Section: Discussionsupporting
confidence: 68%
“…The isocitrate dehydrogenase (IDH) mutation is rare in tumors of patients aged 60 years or more (Louis et al 2016;Hartmann et al 2010); however, the distribution of MGMT promoter methylation is the same in older adults (Wick et al 2012). Median survival in recent large retrospective cohorts of older glioblastoma patients was between 5.3 and 6.2 months (Biau et al 2017;Harris et al 2017;Moroney et al 2017;Smrdel et al 2018). Only one cohort study found a median survival of 10 months in this patient population (Karsy et al 2018).…”
Section: Gliomasmentioning
confidence: 98%
“…GBM represents 15.8% of all brain and CNS tumors (1). Established predictors for long-term survival in GBM include age at diagnosis, baseline Karnofsky Performance Status (KPS), and extent of resection (2)(3)(4)(5). Furthermore, mutations in biological markers are important features to create a reliable prediction of the survival prognosis in GB.…”
Section: Introductionmentioning
confidence: 99%